The alien flora of the Rzeszów Foothills - Jaźwa, Małgorzata; Stadnicka-Futoma, Agata (Biodiversity: Research and Conservation, 2015)
The aim of the study was to analyze the synanthropic flora of the Rzeszów Foothills (south-eastern Poland). Floristic studies were carried out in years 2007-2013 using the cartogram method in the ATPOL system (2×2 km square grid). Here we present the numerical data (number of species in each historical-geographical group, families most frequently represented by anthropophytes), show the proportion of specific growth forms and describe habitat preferences. The Rzeszów Foothills region had already been shown as strongly impacted by anthropogenic pressures. The total number of vascular plant species detected was equal to 1115; among them, the synanthropes represent about 30%. Also the index of synanthropy was calculated to confirm strong anthropogenic transformation of the studied area. In the presented study, 47 invasive plant species were discovered in the region. Moreover, the role and distribution of the most interesting and invasive of the synanthropic species was analyzed based on their negative impact on the native flora. We also identified plant species with high invasive potential and indicated causes of their appearance and spread.